1996
DOI: 10.1128/mcb.16.4.1519
|View full text |Cite
|
Sign up to set email alerts
|

Ku86 Defines the Genetic Defect and Restores X-Ray Resistance and V(D)J Recombination to Complementation Group 5 Hamster Cell Mutants

Abstract: X-ray-sensitive hamster cells in complementation groups 4, 5, 6, and 7 are impaired for both double-strand break repair and V(D)J recombination. Here we show that in two mutant cell lines (XR-V15B and XR-V9B) from group 5, the genetic defects are in the gene encoding the 86-kDa subunit of the Ku autoantigen, a nuclear protein that binds to double-stranded DNA ends. These mutants express Ku86 mRNA containing deletions of 138 and 252 bp, respectively, and the encoded proteins contain internal, in-frame deletions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
117
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 53 publications
11
117
0
Order By: Relevance
“…This agreed well with the results obtained by immunocytochemical analysis (Reeves, 1985;Yaneva et al, 1985;Mimori et al, 1986;Koike et al, 1998). Since both Ku70 and Ku80 monomers are highly unstable compared to their heterodimers (Errami et al, 1996;Gu et al, 1997;Singleton et al, 1997), we were interested in studying the nuclear translocation of Ku80 and its heterodimer partner Ku70. Osipovich et al (1997) reported that mutations in Ku80 corresponding to amino acids 453 and 454 abolished its ability to interact with Ku70, using an in vitro binding assay and the yeast two-hybrid analysis.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This agreed well with the results obtained by immunocytochemical analysis (Reeves, 1985;Yaneva et al, 1985;Mimori et al, 1986;Koike et al, 1998). Since both Ku70 and Ku80 monomers are highly unstable compared to their heterodimers (Errami et al, 1996;Gu et al, 1997;Singleton et al, 1997), we were interested in studying the nuclear translocation of Ku80 and its heterodimer partner Ku70. Osipovich et al (1997) reported that mutations in Ku80 corresponding to amino acids 453 and 454 abolished its ability to interact with Ku70, using an in vitro binding assay and the yeast two-hybrid analysis.…”
Section: Resultssupporting
confidence: 87%
“…Both Ku70 and Ku80 are highly unstable when expressed individually (Satoh et al, 1995). Loss of one of the Ku subunits results in a signiÂźcant decrease in the steady-state level of the other (Errami et al, 1996;Gu et al, 1997;Singleton et al, 1997). These Âźndings strongly suggest that Ku70 and Ku80 function as heterodimers.…”
Section: Introductionmentioning
confidence: 87%
“…31,32 In rodents, Ku DNA binding represents the predominant, if only, mechanism for DNA-PK activation, because the Ku-defective mutants have undetectable DNA-PK activity. 33 Also in rodents, the DNA-PK complex has been shown to play an important role in the response to ionizing radiation, because mutations in one of the DNA-PK subunits lead to an extreme x-ray-sensitivity along with a deficiency in both DSB repair and V(D)J recombination, 34,35 suggesting that the integrity of this complex is necessary for a normal enzymatic activity. It was also possible to complement the deficient phenotype of DNA-PK mutant rodent cell lines by transferring the corresponding genes for Ku86 and DNA-PKcs.…”
mentioning
confidence: 99%
“…It was also possible to complement the deficient phenotype of DNA-PK mutant rodent cell lines by transferring the corresponding genes for Ku86 and DNA-PKcs. [35][36][37] The role of DNA-PK complex in the radiosensitivity of human cells is still being investigated. Interestingly, DNA-PKcs presents a sequence homology in the carboxyl-terminal domain with the ataxia telangiectasia gene (ATM) corresponding to the phosphatidylinositol 3-kinase superfamily catalytic domain.…”
mentioning
confidence: 99%
“…To determine whether Ku might also be important for the activation of PARP-1 subsequent to the DSBs induced by bleomycin, we compared the activity of PARP-1 after treatment in extracts prepared from V79 cells, a hamster embryonic lung fibroblast cell line and V15B cells, a line clonally derived from V79 containing a mutation in the Ku80 gene that leads to the absence of Ku70 and Ku80 (Errami et al, 1996). Typical strong activation of PARP-1 activity was observed in extracts prepared from V79 cells and the response included a shifting and spreading of the PARP-1 band on immunoblots ( Figure 3a).…”
Section: Resultsmentioning
confidence: 99%